Perlindungan Hukum Terhadap Pelaku UMKM dalam Perspektif Hukum Ekonomi - Nuryl, Aqshal; P, Muhammad Rizky; R, Muhammad Viero; Adhyanto, Wira; Siswajanthy, Farahdinny (Sharia Journal and Education Center Publishing, 2026)
Legal protection for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia is crucial to support national economic growth. This study aims to explore the existing legal framework and evaluate the effectiveness of the protection provided to MSMEs from an economic law perspective. The method used is a normative literature review with doctrinal analysis of relevant laws and literature, relying on credible secondary sources. The findings indicate a significant gap between legal norms and actual practices, where MSMEs often find themselves in a weak position due to legal misunderstandings, limited access to financing, and challenges arising in the digital era. The conclusion of this study emphasizes the need for adaptive regulatory reforms, the establishment of an integrated protection agency, and the enhancement of legal literacy for MSME stakeholders. These recommendations are expected to create a fairer and more sustainable ecosystem, boost the competitiveness of MSMEs, and enhance their contribution to the national economy in the face of globalization challenges.